Nozzle tip damage in three generations of intraocular lens injector models: an experimental laboratory study - Zhang, Lu; Schickhardt, Sonja; Merz, Patrick; Auffarth, Gerd U. (BMC ophthalmology, 2023)
To assess the nozzle tip damage of IOL injectors in three generations from the same manufacturer using the self-developed system—the Heidelberg Score for IOL Injector Damage.
Gesehen am 24.03.2023